Generalized keratosis pilaris rubra - Iqbal A. Bukhari; Nada Al Ghamdi; Abdulaziz Al Zahrani; Muhammad Al Shawarby (Our Dermatology Online, 2015)
Generalized Keratosis Pilaris Rubra is a rare dermatosis that is related to Keratosis Pilaris group of disorders. We are reporting a case of Generalized Keratosis Pilaris Rubra in a young Arabic male whom treatment options failed to improve his condition.